2010
DOI: 10.1210/en.2010-0323
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RAGE, NADPH Oxidase, and Ras/Raf-1 Pathway in Glycated LDL-Induced Expression of Heat Shock Factor-1 and Plasminogen Activator Inhibitor-1 in Vascular Endothelial Cells

Abstract: Atherothrombotic cardiovascular diseases are the predominant causes of mortality of diabetic patients. Plasminogen activator inhibitor-1 (PAI-1) is the major physiological inhibitor for fibrinolysis, and it is also implicated in inflammation and tissue remodeling. Increased levels of PAI-1 and glycated low-density lipoprotein (glyLDL) were detected in patients with diabetes. Previous studies in our laboratory demonstrated that heat shock factor-1 (HSF1) is involved in glyLDL-induced PAI-1 overproduction in vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…These effects are likely the result of RAGE activating the cellular signaling pathways that regulate these functions. The main signaling pathways include PI3K (Huang et al 2011), different MAPKs (Tanikawa et al 2009Kim et al 2010;Shang et al 2010), Rho GTPases and ROS (Sangle et al 2010). On the level of transcriptional regulation, NF-jB, AP-1 and Stat3 have emerged as crucial targets of RAGE signaling (Gebhardt et al 2008;Villarreal et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are likely the result of RAGE activating the cellular signaling pathways that regulate these functions. The main signaling pathways include PI3K (Huang et al 2011), different MAPKs (Tanikawa et al 2009Kim et al 2010;Shang et al 2010), Rho GTPases and ROS (Sangle et al 2010). On the level of transcriptional regulation, NF-jB, AP-1 and Stat3 have emerged as crucial targets of RAGE signaling (Gebhardt et al 2008;Villarreal et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is expressed by many different types of cells, including endothelial and vascular smooth muscle cells (Poirier et al, 2001). Extensive evidence indicates that the AGE/RAGE system can promote oxidative stress and activate certain downstream signaling pathways, in particular those involving NOX 2 , a membrane-bound enzyme complex (Sangle et al, 2010;Yamagishi et al, 2012). Our present findings reveal that the levels of both RAGE protein and mRNA are elevated in the brains of rats with chronic fluorosis and in SH-SY5Y cells treated with excessive fluoride, suggesting an activation of the AGE/RAGE pathway by this ion.…”
Section: Discussionmentioning
confidence: 99%
“…AGE has the ability to cause platelet aggregation and fibrin stabilization, resulting in a predisposition to thrombogenesis [59]. RAGE is one of the key factors implicated in the up-regulation of PAI-1 in vascular endothelial cells under diabetes-associated metabolic stress [60]. In the present study, we found that the 82S/S homozygote carriers had a lower sRAGE level, higher IL-6, hs-CRP and PAI-1 levels, suggesting a higher inflammatory status in 82S/S carriers compared with the G/S and G/G genotype carriers.…”
Section: Discussionmentioning
confidence: 99%